2017
DOI: 10.15761/fsc.1000112
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of infrared spectroscopy in examinations of adhesive tapes for forensic purposes

Abstract: Infrared spectroscopy was applied in examination and comparative analysis of adhesive tapes. By providing information about the polymer composition, it enables classification of both backings and adhesives into defined chemical classes. It was found that samples of the same type and similar infrared spectra can be differentiated sometimes based only on the presence of peaks of very low intensity originating from minor components. The results demonstrated that infrared spectroscopy appears to be a valuable anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 13 publications
5
17
0
Order By: Relevance
“…Unprocessed scrub rubber exhibits stretching vibrations corresponding to –CH 3 at 2918 cm −1 , plus a symmetric vibration corresponding to –CH 2 at 2836 cm −1 , a band approximately at 1521 cm −1 for a C=C stretching vibration, and three more bands at 1420, 1338 and 781 cm −1 corresponding to vibrations of CH 2 , CH 3 and C–H groups, respectively. These vibrations are in agreement with what has been reported in the literature [39, 40, 41]. In comparison, the FTIR spectrum of CB nanoparticles obtained by thermal carbonization of scrub rubber presents only the typical band associated to the C–H vibration near to 781 cm −1 and no other vibrational band was detected in the spectrum, indicating the carbonaceous nature of this sample.…”
Section: Resultssupporting
confidence: 91%
“…Unprocessed scrub rubber exhibits stretching vibrations corresponding to –CH 3 at 2918 cm −1 , plus a symmetric vibration corresponding to –CH 2 at 2836 cm −1 , a band approximately at 1521 cm −1 for a C=C stretching vibration, and three more bands at 1420, 1338 and 781 cm −1 corresponding to vibrations of CH 2 , CH 3 and C–H groups, respectively. These vibrations are in agreement with what has been reported in the literature [39, 40, 41]. In comparison, the FTIR spectrum of CB nanoparticles obtained by thermal carbonization of scrub rubber presents only the typical band associated to the C–H vibration near to 781 cm −1 and no other vibrational band was detected in the spectrum, indicating the carbonaceous nature of this sample.…”
Section: Resultssupporting
confidence: 91%
“…Untreated PP media has C-H stretching (2906 cm −1 ), CH2/CH3 asymmetrical bending (around 2982 cm −1 ), and other carbon and hydrogen bonding (2835 to 2972 cm −1 ) peaks To examine whether UV-treated or detergent-laundered respirators changed their chemistry, contact angles and FTIR spectra from those surfaces were examined ( Figure 4B,C). Untreated PP media has C-H stretching (2906 cm −1 ), CH 2 /CH 3 asymmetrical bending (around 2982 cm −1 ), and other carbon and hydrogen bonding (2835 to 2972 cm −1 ) peaks [47,48]. After UV irradiation, distinctive peaks were observed for: C-O-C (around 1058 cm −1 ) and O-H bending (around 1161 cm −1 ) [49,50].…”
Section: Charge Decaymentioning
confidence: 99%
“…However, due to the heterogeneity and characteristics of the sample in the field analysis with the NIR equipment, in some cases FTIR technique in the laboratory was performed as well (Figure 6). The spectra obtained were compared with spectra from the literature of pure polymers (Bozaci et al, 2012;Rodríguez-Bruceta et al, 2014;Smith, 1999;Vahur et al, 2016;Zieba-Palus, 2017). It was found that the absorption peaks coincided with those described for PE, PET, PP, PS and PA by these authors.…”
Section: Identification Of Polymers Existing In Raw Materialsmentioning
confidence: 69%
“…Thus, in the laboratory, this technique was complemented with Fourier Transform Infrared spectroscopy (FTIR), once the materials were washed and dried, to avoid disturbances caused by moisture and dirt. In addition, this equipment provides the values of the main absorption peaks, which allows comparing them with those in the literature (Bozaci et al, 2012;Rodríguez-Bruceta et al, 2014;Smith, 1999;Vahur et al, 2016;Zieba-Palus, 2017) and confirming the type of polymer that compose the waste. The analysis was performed with a Perkin-Elmer FT-IR Spectrometer model Spectrum 65, which has a wavelength range of 4000-400 cm -1 and a resolution of 2 cm -1 .…”
Section: Characterization Of Raw Materials In the Treatment Plant Andmentioning
confidence: 99%